Fluid intake impact on heart failure: Systematic review and meta-analysis with trial sequential analysis - Suh-Meei Hsu; Yueh-Hung Lin; Ying-Chun Lin; Shu-Jung Liu; Chih-Ju Liu; Chung-Lieh Hung; Tsae-Jyy Wang (Journal of the Formosan Medical Association)
Background: Heart failure (HF) management lacks clarity regarding fluid balance strategies, with some studies suggesting potential benefits of liberal fluid intake. This review aims to evaluate both unrestricted and restricted fluid intake, including sodium restriction, in adult HF. Methods: A thorough search of electronic databases, including PubMed, MEDLINE, and Cochrane Library, identified relevant studies examining fluid intake effects on adult heart failure patients, categorized by liberal or restricted intake, with subgroup analysis on sodium restriction. Pooled odds ratios (OR) and weighted mean differences (WMD) were calculated, employing trial sequential analysis (TSA) for reliability. Nine studies involving 961 patients were included, with follow-up durations ranging from 2 days to 6 months. Results: Daily fluid intake ranged from 0.8 to 1.5 L for the intervention group, and sodium intake varied from 2.0 to 5.0 g per day across five studies. No significant differences were observed in re-hospitalization rate, mortality rate, thirst, quality of life, doses of diuretics, or serum sodium levels between liberal and restricted intake groups. However, fluid-restricted patients exhibited increased serum creatinine levels, decreased serum B-type natriuretic peptide (BNP) levels and reduced body weight. Conclusion: In summary, the existing studies on this topic are hindered by heterogeneity and relatively small sample sizes. However, when the available data is combined, it suggests that HF patients managed with either liberal or restrictive fluid intake exhibit similar clinical outcomes. It's worth noting that fluid restriction in HF patients might lead to increased serum creatinine levels, decreased BNP and body weight.